The Level of Knowledge and Demographics of Older Adults with Type 2 Diabetes: A Comparative Study - Ico, Jhancy; Aviles, Jhamina Kim; Carretero, April Joy; De Guzman, Annacil; Domantay, Joan Maricon; Repollo, Maxeene Jomaira; Llego, Jordan (MALATA SAINS INDONESIA, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a major global public health concern, accounting for 90–95% of diabetes cases and affecting an estimated 537 million adults worldwide, a number projected to rise to 783 million by 2045. Objective: This study aims to determine differences in knowledge and demographic characteristics among older adults with Type 2 diabetes mellitus (T2DM) in two villages in Dagupan City. Methods: A total of 100 respondents completed the Filipino Version of the Michigan Diabetes Knowledge Test. Purposive sampling was employed. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were used. Inferential statistics were applied to test for significant differences. Results: The findings revealed that participants demonstrated good awareness of the risks associated with high-fat diets but had limited knowledge regarding the effects of unsweetened fruit juices and “free foods” on blood glucose control. Overall, respondents exhibited a moderate level of understanding of diabetes care. Notable gaps were identified in insulin-related knowledge, particularly in managing comorbid conditions such as influenza. No significant differences in knowledge were observed across age groups and educational attainment. However, a significant difference was found between genders, indicating the need for gender-sensitive educational approaches. Conclusion: Overall, the study emphasizes the need to identify and address knowledge deficiencies in diabetes treatment in older adults. The research highlights the importance of tailored, culturally sensitive, and gender-specific educational programs in enhancing diabetes awareness among older adults. Nurses have a key role in delivering these interventions, which could have a substantial influence on diabetes control and the quality of life for this group.